“With the humble is wisdom”: humility as an antidote to humiliation and shame - Richards, Barry (Interdisciplinary applications of shame/violence theory, 2022)
Humility is of deep significance for the functioning of democratic societies, as it is the psychic basis of the capacity to function in a citizenly way. Its meaning as the opposite of humiliation shows a deep ambiguity in the resonances today of the Latin word humus (meaning ground or soil) which is the source of both terms. Psychoanalytically, this ambiguity can be seen as reflecting a basic choice we repeatedly make in our psychological functioning. On the one hand is the inability to trust others, and the consequent narcissistic illusions of a fully independent self which can escape the humiliation which dependence on others is felt to bring. On the other hand, there is sufficient trust in others to accept the self’s dependence on human society, and so to accept the inevitability of vulnerability and limitation. This toleration of reality involves a state of humility or humbleness. Humility is therefore an antidote to the fear of humiliation, which is a key driver of many forms of violence, including terrorism. The article ends with a consideration of whether strengthening resources of humility could be a helpful contribution to containing violent behaviour.